Adherence to Mediterranean diet in HIV infected patients: relation with nutritional status and cardiovascular risk - Policarpo, Sara (2017)
Background & aims: The Mediterranean diet (MedDiet) has been associated to a lower prevalence of metabolic syndrome (MS) and a lower cardiovascular risk (CVR). Our aim was to assess HIV infected individual's adherence to the MedDiet and its relationship with nutritional status and CVR. Methods: Clinical and anthropometric data were collected and a nutritional assessment was performed. Adherence to the MedDiet was assessed using the questionnaire MedDietScore, ranging from 0 to 55, where higher scores indicated a higher adherence. CVR was estimated for each patient using the Framingham Risk Score (FRSs-CVD). Results: We included 571 individuals, mostly males (67.1%; n = 383). MedDiet adherence score was 27.5 ± 5.5 points. The proportion of overweight/obese individuals was 40.3% (n = 230) and MS 33.9% (n = 179); CVD estimation showed that 53.2% (n = 304), 30.1% (n = 172) and 16.6% (n = 95) of patients had a low, moderate and very high CVR, respectively. The group with BMI below 25 kg/m2 presented lower adherence to MedDiet and patients within moderate CVR category and with MS presented a higher adherence to MedDiet. Conclusions: Overall we found a moderate adherence to the Mediterranean diet. A higher adherence was associated to individuals with a BMI ≥ 25 kg/m2, those with MS and to patients with moderate to high cardiovascular risk, suggesting the adoption of this food pattern in the presence of comorbidities.